Effect of Head Elevation 30° on GCS Value, and Oxygen Saturation in Stroke Patients - Kiswanto, Logi; Chayati, Nur (JOSING: Journal of Nursing and Health, 2022)
This study aims to determine the effect of applying 30° head elevation to increase oxygen saturation and GCS scores in stroke patients. The research method is a systematic review by searching for articles through Pubmed, Google Scholar, Proquest, Emerland, and Garuda. The results showed that the number of articles synthesized was eight, with the result that there were 4 GCS scores and SP02 scores of 2.48% after 30 head elevation. In conclusion, 30° head elevation affects the GCS value and oxygen saturation. Keywords: Head Elevation 30°, Oxygen Saturation, Stroke